Clinical and Research Activities at the CATANA Facility of INFN-LNS: From the Conventional Hadrontherapy to the Laser-Driven Approach - Cirrone, Giuseppe A. P.; Cuttone, Giacomo; Raffaele, Luigi; Salamone, Vincenzo; Avitabile, Teresio; Privitera, Giuseppe; Spatola, Corrado; Amico, Antonio G.; Larosa, Giuseppina; Leanza, Renata; Margarone, Daniele; Milluzzo, Giuliana; et al. (Frontiers in Oncology, 2017)
The CATANA protontherapy center was the first Italian clinical facility making use of energetic (62 MeV) proton beams for the radiative treatment of solid tumours. Since the date of the first patient treatment in 2002, 400 patients have been successful treated whose majority was affected by choroidal and iris melanomas. In this paper we report on the actual clinical and physical status of the CATANA facility describing the last dosimetric studies and reporting on the last patient follow-up results. The last part of the paper is dedicated to the description of the INFN ongoing activities on the realisation of a beamline for the transport of laser-accelerated ion beams. The ELIMED (ELI-BEamlines MEDical and multidisciplinary applications) project is intruded and its main scientific aspects described.